2022
DOI: 10.1111/nph.18104
|View full text |Cite
|
Sign up to set email alerts
|

Impaired KIN10 function restores developmental defects in the Arabidopsis trehalose 6‐phosphate synthase1 (tps1) mutant

Abstract: Sensing carbohydrate availability is essential for plants to coordinate their growth and development. In Arabidopsis thaliana, TREHALOSE 6-PHOSPHATE SYNTHASE 1 (TPS1) and its product, trehalose 6-phosphate (T6P), are important for the metabolic control of development. tps1 mutants are embryo-lethal and unable to flower when embryogenesis is rescued. T6P regulates development in part through inhibition of SUCROSE NON-FERMENTING1 RELATED KINASE1 (SnRK1).Here, we explored the role of SnRK1 in T6P-mediated plant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 74 publications
3
39
0
Order By: Relevance
“…Consistent with negative regulation of SnRK1 activity by T6P (Zhang et al, 2009), the tps1 mutant, deficient in the major T6P synthase TPS1 (Eastmond et al, 2002; Van Dijken et al, 2004), shows significantly reduced anthocyanin accumulation and MYB75 and DFR expression in sucrose-rich medium (Figure 2C,D). Moreover, the recently described tps1 suppressor mutants with additional mutations in the SnRK1α1 catalytic site (160-1: G178R, 199-6: R259Q, 232-2: G162D) and concomitant restoration of embryogenesis and transition to flowering (Zacharaki et al, 2022) showed a fully restored sucrose-induced anthocyanin biosynthesis and MYB75 and DFR expression (Figure 2E,F). Together, our results confirm that SnRK1 is an important negative regulator of sucrose-induced anthocyanin biosynthesis, at least in part by transcriptional repression of MYB75 , a key factor in controlling expression of DFR , an essential enzyme for anthocyanin biosynthesis.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Consistent with negative regulation of SnRK1 activity by T6P (Zhang et al, 2009), the tps1 mutant, deficient in the major T6P synthase TPS1 (Eastmond et al, 2002; Van Dijken et al, 2004), shows significantly reduced anthocyanin accumulation and MYB75 and DFR expression in sucrose-rich medium (Figure 2C,D). Moreover, the recently described tps1 suppressor mutants with additional mutations in the SnRK1α1 catalytic site (160-1: G178R, 199-6: R259Q, 232-2: G162D) and concomitant restoration of embryogenesis and transition to flowering (Zacharaki et al, 2022) showed a fully restored sucrose-induced anthocyanin biosynthesis and MYB75 and DFR expression (Figure 2E,F). Together, our results confirm that SnRK1 is an important negative regulator of sucrose-induced anthocyanin biosynthesis, at least in part by transcriptional repression of MYB75 , a key factor in controlling expression of DFR , an essential enzyme for anthocyanin biosynthesis.…”
Section: Resultsmentioning
confidence: 69%
“…Arabidopsis thaliana mutant lines were in the Col-0 or Ler background. The Ler SnRK1α1 OX, SnRK1α1 RNAi (Baena-González et al, 2007), dfr1 ( tt3-1 ; NASC NW84) and Col-0 pap1-D (Borevitz et al, 2000), myb75 RNAi (Jover-Gill et al, 2014), ttg1-21 (GK-580A05; NASC N2105595), ttg1-22 (GK-286A06; NASC N330696), tps1 (Van Dijken et al, 2004), tps1 suppressor (Zacharaki et al, 2022) and NLS-SnRK1α1 and βMYR-SnRK1α1 (Ramon et al, 2019) mutants and transgenic lines have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…TRIOSE PHOSPHATE ISOMERASE (TPI) promotes the transition of plants from heterotrophic growth to autotrophic growth [ 62 ]. The Arabidopsis snf4 mutation disrupts the interaction of SNF4 with SNRK1 and thus affects the role of SNRK1 in the T6P-mediated signaling pathway [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tre and its precursor T6P have diverse and vital functions in plants, linking growth and development to carbon status [ 30 , 31 ]. As an important enzyme in T6P synthesis, TPS1 is also essential for normal vegetative growth and transition to flowering, and the deletion of TPS1 prevents floral transition in Arabidopsis [ 32 , 33 ]. They were reported to play important roles in maize early kernel development and events leading to stress-induced kernel abortion [ 34 ].…”
Section: Discussionmentioning
confidence: 99%